قيم الخضاب والولادة الباكرة (مجلة جامعة اللاذقية - سلسلة العلوم الصحية, 2019)
أجريت هذه الدراسة على 832 حامل في قسم التوليد بمشفى الأسد الجامعي باللاذقية في الفترة ما بين 1/7/2006 و 1/7/2007. قسمت الحوامل إلى أربع مجموعات: المجموعة الأولى 54 قيم خضابهن أقل من 9غ/دل, المجموعة الثانية 82 تتراوح قيم الخضاب عندهن بين 9-10 غ/دل, المجموعة الثالثة قيم الخضاب عندهن تتراوح بين 10-11 غ/دل والمجموعة الرابعة 502 قيم الخضاب عندهن أكبر من 11 غ/دل. وكان هدف هذه الدراسة تحديد نسبة حدوث الولادة الباكرة في كل مجموعة. إن الولادة الباكرة كانت بنسبة 18.51 % في المجموعة الأولى مقابل 15.85% في المجموعة الثانية, 12.37% في المجموعة الثالثة و 9.16% في المجموعة الرابعة. This study has been carried out on 832 pregnant women in Obstetric and Gynecology Department at AL-Assad University Hospital in Lattakia between 1/7/2006 and 1/7/2007. They were divided into four groups: the first group consisted of 54 cases, and their hemoglobin was < 9 g/dl; the second group comprised 82 cases, and their hemoglobin was between 9 and 10 g/ dl; the third group included 194 pregnant women, and their hemoglobin was between 10 and 11 g/ dl, and the fourth group comprised 502 pregnant women, and their hemoglobin was > 11 g/ dl. The purpose of this study was to determine the premature delivery ratios for each group; the ratios of premature delivery were 18.51% in the first group versus 15.85% in the second,12.37% in the third, and 9.16% in the fourth.